Brazilian guidelines for the treatment of outpatients with suspected or confirmed COVID-19. A joint guideline of the Brazilian Association of Emergency Medicine (ABRAMEDE), Brazilian Medical Association (AMB), Brazilian Society of Angiology and Vascular Surgery (SBACV), Brazilian Society of Geriatrics and Gerontology (SBGG), Brazilian Society of Infectious Diseases (SBI), Brazilian Society of Family and Community Medicine (SBFMC), and Brazilian Thoracic Society (SBPT) - Falavigna, Maicon; Belli, Karlyse Claudino; Barbosa, Alexandre Naime [UNESP]; Zavascki, Alexandre Prehn; Nastri, Ana Catharina de Seixas Santos; Santana, Christiane Machado; Stein, Cinara; Gräf, Débora Dalmas; Cadegiani, Flavio Adsuara; Guimarães, Hélio Penna; Monteiro, José Tadeu; Ferreira, Juliana Carvalho; et al. (Elsevier, 2022)
Background: Several therapies have been used or proposed for the treatment of COVID-19, although their effectiveness and safety have not been properly evaluated. The purpose of this document is to provide recommendations to support decisions about the drug treatment of outpatients with COVID-19 in Brazil. Methods: A panel consisting of experts from different clinical fields, representatives of the Brazilian Ministry of Health, and methodologists (37 members in total) was responsible for preparing these guidelines. A rapid guideline development method was used, based on the adoption and/or adaptation of recommendations from existing international guidelines combined with additional structured searches for primary studies and new recommendations whenever necessary (GRADE-ADOLOPMENT). The rating of quality of evidence and the drafting of recommendations followed the GRADE method. Results: Ten technologies were evaluated, and 10 recommendations were prepared. Recommendations were made against the use of anticoagulants, azithromycin, budesonide, colchicine, corticosteroids, hydroxychloroquine/chloroquine alone or combined with azithromycin, ivermectin, nitazoxanide, and convalescent plasma. It was not possible to make a recommendation regarding the use of monoclonal antibodies in outpatients, as their benefit is uncertain and their cost is high, with limitations of availability and implementation. Conclusion: To date, few therapies have demonstrated effectiveness in the treatment of outpatients with COVID-19. Recommendations are restricted to what should not be used, in order to provide the best treatment according to the principles of evidence-based medicine and to promote resource savings by aboiding ineffective treatments.
Keywords: Brazil; COVID-19; COVID-19 drug treatment; GRADE; Guideline; SARS-CoV-2